The Effect of Shotblocker Use on Pain Scores in Infants Undergoing Intramuscular Immunization at Jatinangor Primary Health Center - Syahla Jahda Syahidah; Ida Widiawati; Santi Sofiyanti; Rika Resmana (Jurnal Kebidanan, 2026)
Pain caused by immunization procedures often leads to anxiety, fear, and even trauma in children, potentially affecting their adherence to the immunization schedule. Shotblocker is a simple device based on the Gate Control Theory, which reduces pain perception through tactile stimulation. This study aimed to determine the effect of Shotblocker use on pain scores among two-month-old infants receiving intramuscular immunization. A quasi-experimental design with a posttest-only control group was employed on 80 infants, divided into an intervention group (with Shotblocker) and a control group (without Shotblocker). Pain was assessed using the FLACC scale. The results showed that the mean pain score in the intervention group was 3.57 (SD = 0.879), while in the control group it was 6.48 (SD = 0.727). An independent sample t-test indicated a significant difference between the groups (p < 0.05). These findings demonstrate that Shotblocker significantly reduces pain intensity in infants following intramuscular immunization. Shotblocker may serve as a safe and effective non-pharmacological tool to improve pediatric comfort.